Comparación del desempeño de las exportaciones no tradicionales entre Loreto y San Martín periodo 2019-2023 - Padilla Diaz, Daneri Steffi (2025)
This study aimed to compare the performance of non-traditional exports between the regions of Loreto and San Martín during the period 2019-2023. The research was basic in type, descriptive in level, with a non-experimental and longitudinal design. The study worked with secondary data extracted from the official databases of SUNAT/Aduanas, considering the totality of non traditional export records from both regions as the analysis sample. The results showed that San Martín exported a total of 619.2 million dollars, while Loreto reached 49.4 million dollars, confirming a significant gap. The average annual growth rate was +23.78% in San Martín and -12.78% in Loreto, reflecting a more stable performance in the former. San Martín specialized in cocoa and palm oil, while Loreto focused on ornamental fish and reptiles. Regarding markets, San Martín prioritized regional destinations such as Colombia and Chile, while Loreto directed its shipments to distant markets like China and Russia. At the business level, San Martín displayed a high concentration in a leading company, while Loreto presented a fragmented structure with smaller export companies. It is concluded that the performance of non-traditional exports differs significantly between Loreto and San Martín, highlighting the need for differentiated strategies to strengthen the competitiveness and sustainability of both regions in international trade.